Marketing Mix: Costumer Decisions in Choosing Simpeda Savings at Sulselbar Bank - Amir Mahmud; Nurmiati (LAA MAISYIR: Jurnal Ekonomi Islam, 2022)
This study departs from the problem that whether the marketing mix has a simultaneous and partial effect on customer decisions to use the simpeda product. The aim is to find out and analyze how much influence the marketing mix (7P) has on customer decisions in choosing SIMPEDA products at PT. Bank Sulselbar Mamuju Main Branch and the most dominant variable. This research approach is quantitative. The sampling technique is incidental sampling with a total of 100 respondents. The results showed that the product, price, place, promotion, people, physical evidence and process variables simultaneously had a positive and significant effect on customer decisions in choosing SIMPEDA Savings at PT. Bank Sulselbar Mamuju Main Branch. Meanwhile, the T-test results show that the product, price, promotion and process variables partially have a positive and significant effect. While the variables of place, person and physical evidence partially have no effect and are not significant. The dominating variable is promotion has a positive and significant effect in choosing SIMPEDA Savings at PT. Bank Sulselbar Mamuju Main Branch.